Non-invasive monitoring of curd syneresis upon renneting of raw and heat-treated cow's and goat's milk. (March 2019) - Curti, Elena; Pardu, Alessandra; Del Vigo, Stefania; Sanna, Roberta; Anedda, Roberto
Abstract: Molecular mobility of water during curd syneresis was investigated in raw and heat-treated cow's and goat's whole milk by Time-Domain 1 H Nuclear Magnetic Resonance (TD-NMR). Rennet was added to raw and heat-treated (72 °C) milk inside the NMR magnet at 40 °C, and curd evolution was monitored non-invasively over time. Distributions of 1 H NMR spin–spin relaxation time constants (T2 ) were obtained at time zero (just after rennet addition), after 30 min (complete curd coagulation) and during serum expulsion (syneresis), every 10 min up to 70 min. Relaxation times and abundances of detected 1 H populations were calculated at each time point. Although further statistical validation would require a larger sample number, raw and heat-treated milk and the corresponding curd samples showed different NMR behaviour. It can be concluded that TD-NMR is able to identify differences between the molecular dynamics characterising raw milk and curd, and their heat-treated counterparts.